Fear of Floating and Inflation Targeting in Turkey - Vasif Abiyev; Munise Ilıkkan Özgür (International Journal of Economic Sciences and Applied Research, 2014)
The objective of this paper is to test empirical validity of Fear of Floating hypothesis for Turkey after the adoption of Inflation Targeting. We start applying methodologies developed by Calvo and Reinhart (2002) and Ball and Reyes (2004, 2008) to check the probabilities of changes in exchange rate and monetary policy instruments before and after inflation targeting regime. We then use a VAR model to estimate exchange rate pass-through and response of monetary policy instruments to exchange rate shocks before and after inflation targeting regime. VAR model helps to understand the impacts of switch in monetary policy regime on exchange rate pass-through and foreign exchange market interventions. The paper concludes that after the adoption of inflation targeting regime, the exchange rate pass-through still matters for the attainment of inflation targets and the monetary policy do not exhibit a fear of floating practices.
Keywords: F31; E31; E58; 330; Fear of floating; fear of inflation; exchange rate pass-through; free floating exchange rate